THE CURRENT STATE AND PRINCIPLES OF THE FORMATION OF THE TOURIST AND RECREATION POTENTIAL OF THE KHMELNYTSKY REGION - ZHURBA, IGOR; HRUNDIJ, OKSANA; HRYHORIEVA, LIUDMYLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the main directions of systemic combination and complementarity of the tourist and recreational potential of Khmelnytsky region on the basis of the region's tourism development center. The existing tourist flows and recreational and tourist resources, which are already used in the market, were analyzed. It was found out which types of tourism are the most potentially appropriate for the Khmelnytsky region and on the basis of which resources the recreational and tourist potential should be formed. In order to prolong the stay of tourists and visitors in the region, it is necessary to support the effective use of mineral waters and other healing resources; improvement of conditions of access to financing of tourism development projects; creation of attractive facilities for children, sports and recreation, infrastructural improvement of territories adjacent to tourism facilities. It is the duty of each participant in the tourism product chain to strive to improve tourism facilities and tourism products using marketing as a tool to attract and retain tourists in the region. The presence of mineral springs, basic sanatoriums, as well as the presence of vacationers in the resorts of the neighboring Vinnytsia, Ternopil, and Lviv regions makes it possible to involve them in historical and architectural tourism at the tourist sites of the Khmelnytsky region. The landscapes and nature of Transnistria and Tovtr are promising for the development of recreational tourism. Historical and architectural sights of the Middle Ages of Kamianets-Podilsky can be included in international tourism tours.
Keywords: recreation; object of tourism; type of tourism; tourism and recreation potential; tourist flow